MINERALOGY OF VIVIANITE FROM ROSIA POIENI; METALLOGENETIC SIGNIFICANCE (PANGEEA, 2025)
Mineralogy of Vivianite from Rosia Poieni; Metallogenetic significance. The deposit at Rosia Poieni is the largest accumulation of copper in M. Metaliferi, in Southern Apuseni Mountains. By the side of Cu, in paragenesis appear Au and Te that, among other elements, forms its own minerals. These are rare minerals and were studied because they have a special scientific and economic importance. Among these minerals include Vivianite, which was discovered in Rosia Poieni ore which is described in the paper. Positive correlation has been observed between Cu/Te and Cu/Au ratios for pyrite-hosted fluid inclusions in Rosia Poieni ore deposit (Kouzmanov et al, 2004). A similar trend was established by Wallier (2004) & Rey (2004) – in their master thesis, for low-salinity epithermal fluids in the intermediate-sulfidation neighboring epithermal Au-Ag deposit of Rosia Montana, thus suggesting a possible genetic link between the two deposits. Vivianite Fe2+3(PO4)2.8H2O is one of the significant hydrothermal components, especially in the lower south-west part of the open pit (fig. 2), where vivianite occurs as dark-blue prismatic crystals of up to 6 cm in length, against a background of mainly argillic (subordinately potassic and silicic) hydrothermal and supergene alteration affecting host microdiorites. The newly described vivianite occurrence might be similar with the one described in Musca gallery which intersected the lower part of Rosia Poieni complex (Giusca and Pavelescu, 1954). Larger crystals of vivianite occur in veinlets or vugs, associated with quartz, pyrite, chalcopyrite, enargite and a yellowish argillic matter (Figures 3, 4 and 5). Thin films of vivianite may also occur along fine fissures in silicified, dark-gray microdiorites and on cleavage planes of hydrothermalized Cretaceous sedimentary rocks. Based on the physiographic relationship with the other minerals, vivianite appears to be the last hydrothermal mineral.
Keywords: accumulation; paragenesis; rare minerals; Vivianite